Development of Hygyene and Sanitation Learning Tools Based on Typical Food “Mbohi Dungga” Using PBL Model to Improve Students' Creative Thinking Ability - Mahfud, Mahfud; Feriyadin, Feriyadin (Sean Institute, 2022)
Research on hygiene and sanitation courses has been carried out on students of the tourism study program at STIPAR Soromandi Bima. This study aims to develop a hygiene and sanitation learning tool based on typical food